Customer satisfaction towards sales services provided by showroom sales staff at Sime UEP Properties Berhad Subang Jaya / Hasrol Amri Abu Yazid - Abu Yazid, Hasrol Amri (Faculty of Business and Management, 2006)
Organizations cannot exist without customers. As such, the customer must be the central focus of the organization. Goals around market share and diversity, profit yield, and so on, are directly related to customer patronage.